The New Austrian School challenge to Keynesian demand management - Brett Fiebiger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
After the global financial crisis, the Bank for International Settlements emerged as an influential voice in policy debates. Under the rubric of preventing 'financial imbalances', and concerned with the 'illusory' nature of demand management, the Bank has proposed a macro policy framework based on 'finance-neutral' output gaps. This paper critiques the analysis of the New Austrian School, that is, the Bank for International Settlements. The Bank is seeking an operational anchor for a Hayekian version of the Wicksellian 'natural rate of interest' that would obtain a 'sustainable' output level consistent with a long-run 'financial equilibrium' for the private non-financial sector. The fuzzy concept of 'financial imbalances' plays a similar role to that of 'forced saving' in the Old Austrian School framework. Incredibly, the institutional flaws in the eurozone that made sovereigns vulnerable to debt crises, large current-account surpluses, high rates of unemployment and rising inequality are not deemed as 'imbalances' worthy of a public policy response.
Keywords: B13; B25; B53; E20; E32; E51; 330; financial imbalances; Austrian school; natural rate of interest; fiscal policy